A comparison of long-term clinical outcomes between PCI and medical therapy in patients with chronic total occlusion in non-Infarct-related arteries after AMI PCI. (14th October 2021) - Qin, Q; Ma, J; Ge, J
Abstract: Background: Chronic total occlusion (CTO) in a non-infarct-related artery (IRA) is one of the risk factors for mortality after acute myocardial infarction (AMI). However, there are limited data comparing the long-term outcomes of patients underwent successful percutaneous coronary intervention (s-PCI) with patients having medical therapy (MT) in CTO lesion after AMI PCI. Methods: We retrospectively enrolled 330 patients (n=166 in s-PCI group and n=164 in MT group) with CTO in a non-IRA from a total of 4372 patients who underwent PCI after AMI from July 2011 to July 2019 in our center (Figure 1). Propensity matching (119 matched pairs) was used to adjust for baseline differences. Major adverse cardiovascular and cerebrovascular events (MACCEs) on follow-up were defined as the composite of cardiac death, all cause death, myocardial infarction (MI), stroke and any revascularization. Kaplan-Meier analysis were used to evaluate the long-term outcomes between s-PCI and MT group. Results: The patients in MT group were older, more likely to be diagnosed as STEMI, had lower eGFR and higher peak troponin T level during AMI compared with s-PCI group. Furthermore, in MT group, the involvement of LAD as IRA (50.6% vs 38.6%, p=0.028) and LCX as CTO vessel (45.1% vs 27.1%, p=0.001) was more frequent than in s-PCI group, and thus the involvement of LAD as CTO vessel was less frequent (28.9% vs 39.8%, p<0.001). During a median follow-up period of 946 days, patients in s-PCI group had significantly lower incidences of cardiac death (3.0% vs 10.4%, p=0.017) and all cause death (5.4% vs 14.0%, p=0.030) when compared with patients in MT group. Moreover, after PSM, patients in s-PCI group still showed lower incidence of cardiac death (2.5% vs 9.2%, p=0.04). The incidence of MI, stroke, revascularization and MACCE showed no significant difference between the two groups both before and after PSM. In multivariate analysis, age (HR 1.06, 95% CI 1.02–1.10, p=0.003) and LVEF<50% (HR 4.71, 95% CI 1.72–12.90, p=0.003) showed significant correlation with long term cardiac death, however, successful CTO PCI showed borderline significance (HR 0.42, 95% CI 0.15–1.16, p=0.095). In subgroup analysis, Kaplan–Meier curve showed s-PCI group had a lower incidence of cardiac death compared with MT in patients with LVEF<50% both before (p=0.011) and after PSM (p=0.045). However, no difference was observed between two groups in patients with LVEF≥50%. Conclusions: In our center, s-PCI of CTO in non-IRA after AMI PCI showed better long-term cardiac survival as compared with MT. Moreover, patients with low LVEF may be benefit from CTO PCI in non-IRA. Funding Acknowledgement: Type of funding sources: None.